A Grounded Theory of Professional Learning in an Authentic Online Professional Development Program - Teräs, Hanna; Kartoğlu, Ümit (International Review of Research in Open and Distributed Learning, 2017)
Online professional development (OPD) programs have become increasingly popular. However, participating in professional development does not always lead to profound professional learning. Previous research endeavours have often focussed on measuring user acceptance or on comparing the effectiveness of OPD with a face-to-face delivery, but there is little knowledge of how the process of professional learning actually occurs in OPD. This study explores how professional learning takes place in an OPD program designed according to the principles of authentic e-learning, and how the learning design and technologies used impact on the professional learning experienced by the participants. The context of the study is an international OPD program in vaccine management developed and offered by World Health Organization. A grounded theory approach was employed to develop a theorised model of the professional learning process in an authentic online learning environment. The findings show that professional learning was facilitated in a dynamic web of interactions rather than by covering content: the learner is at the centre of the process, actively engaged in authentic tasks in collaboration with peers, while mentors and content play a supporting role. Technology facilitates and enables the web of interactions. The learning process was found to bear resemblance to the type of professional learning that occurs in authentic workplace settings, which implies that the authentic e-learning principles provide a helpful learning design framework for OPD.